[Mandaya ethnic music] (NCCA, 1990)
A demonstration of the Mandaya musical instruments such as the Bayok (chant), gimbas (drum), Bonabon (flute), Kudlong (2-stringed flute), suding (Jew's harp) and the ethnic dance.